Bibliometric analysis of publications on wine tourism in the databases Scopus and WoS - Amador Durán Sánchez; María de la Cruz Del Río Rama; José Álvarez García (European Research on Management and Business Economics, 2017)
The aim of this study was to show the current state of scientific research regarding wine tourism, by comparing the platforms of scientific information WoS and Scopus and applying quantitative methods. For this purpose, a bibliometric study of the publications indexed in WoS and Scopus was conducted, analyzing the correlation between increases, coverage, overlap, dispersion and concentration of documents. During the search process, a set of 238 articles and 122 different journals were obtained. Based on the results of the comparative study, we conclude that WoS and Scopus databases differ in scope, data volume and coverage policies with a high degree of unique sources and articles, resulting both of them complementary and not mutually exclusive. Scopus covers the area of wine tourism better, by including a greater number of journals, papers and signatures.